2020
DOI: 10.21203/rs.3.rs-38745/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sexual Function and Metabolic/Hormonal Changes in Women Using Long-Term Hormonal and Non-Hormonal Contraceptives: A pilot study.

Abstract: Background: Female sexual dysfunction is a common condition that negatively impacts the emotional health and quality of life of the affected individuals. Long-acting reversible contraceptives (LARCs) are becoming increasingly popular due to their effectiveness and convenience. LARCs can be hormonal (etonogestrel releasing implant—ENG and Levonorgestrel intrauterine system—LNG) or non-hormonal (copper intrauterine device—CuIUD and copper-silver intrauterine device—SIUD). There are very few studies that assess t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…regarding IUCD, the current study showed non-significant difference between IUCD users and controls regarding total and domain scores of FSFI. Similarly, the study of Moreira et al (28) showed that sexual function not significantly changed after using either CuIUD (copper intrauterine device), SIUD group (silver intrauterine device) for 3 months with non-significant data suggesting an improvement in sexual function.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…regarding IUCD, the current study showed non-significant difference between IUCD users and controls regarding total and domain scores of FSFI. Similarly, the study of Moreira et al (28) showed that sexual function not significantly changed after using either CuIUD (copper intrauterine device), SIUD group (silver intrauterine device) for 3 months with non-significant data suggesting an improvement in sexual function.…”
Section: Discussionmentioning
confidence: 83%
“…Indeed the current findings can be attributed to the fact that these devices can reduce the fear of unwanted pregnancy, promoting a more relaxed and pleasurable sexual experience and, thus, improving the user's sexual function. This may be possible because a satisfactory sexual response and the perception of sexual pleasure during intercourse is influenced by a complex multifactorial set, involving biological, psychological, and environmental factors (28) .…”
Section: Discussionmentioning
confidence: 99%